Contributing Factors to The Students’ Speaking Ability - Irwan Malin Basa; Deni Asrida; Novria Fadli (Langkawi: Journal of The Association for Arabic and English, 2017)
The use of English in Indonesia has developed quickly in all of fields. It’s affected by many things in many ways. The need of English has also increased quickly in many parts of indonesians’ life. In order to face its, teaching English at young ages or student seems like the solution. Speaking is one of the skills that should be tough to the student. To get an effective learning, it’s useful to know what are factors contributing to the student speaking development. This research showed that there are some contributing factors to the students’ speaking development. Those factors are: Teacher, Daily Practice, Listening to English Music, Family Support, Watching English Video and Movie, Motivation to Learn, Classroom Environment, Learning Material. Such as a good teacher would provide a good learning. Support of the family would also give an effective outcome for the students development. So, the factors should be known in order to get a better outcome for the students.